PRESEPSI MAHASIWA TERHADAP TATTOO DI TUBUH MANUSIA: STUDI KASUS MAHASISWA PEREMPUAN FISIP UNTAG SURABAYA - Puspa, Jeannette Sarita; Darmawan, Arif; Pratiwi, Ni Made Ida (representamen, 2015)
Tattoo is a work of human art known since ancient times . There is no definitive information aboutthe emergence of this self sculpture. But certainly have become entrenched and people's lifestyles inalmost all corners of the world. Posed artistic beauty wowed some communities , which raises the fancommunity group , to users of this tattoo. Based on the background of the above problems, theformulation of the problem of this research is how the student perception UNTAG against tattoos on thebody. This study used a qualitative descriptive method by distributing questionnaires to a samplewithdrawal . Samples in this study were female students of the Faculty of Social and Political SciencesUniversity August 17, 1945 in Surabaya.Keywords : Tattoo , tattoos perceptions